Integrating circular economy into STEM education: A promising pathway toward circular citizenship development - Nguyen, Thi Phuoc Lai (Frontiers in Education, 2023)
The young generation is expected to address current development challenges. The main challenge of sustainable development is the problem of waste management and recycling. To promote long-term sustainability, it is crucial to equip youth with contemporary knowledge and skills and to change their daily habits. The Circular Economy (CE) has become a key concept in responding to unsustainable resource use and waste management globally. At the same time, Science, Technology, Engineering, and Math (STEM) education is an innovative teaching approach to promote learners’ capacity for self-direction, problem-solving, collaboration, and management. This paper argues the role of STEM education in connecting science with society, the benefits of teaching CE in promoting sustainable consumption and production behaviors, and the potential integration of CE into STEM education through real-world context inquiry and real-world problem-solving. It also presents the case of Vietnam, where integration of STEM education and CE in secondary schools is crucial for a CE toward sustainable development. Questionnaire surveys with 873 secondary school teachers and semi-structured interviews with 54 were conducted during the integrated STEM professional trainings. The aims were to examine teachers’ perspectives on the relevance of STEM education and CE to sustainable development and their behaviors toward integrating CE concepts into daily STEM teaching activities. The findings showed a high perception of STEM teachers on the relevance of CE with STEM teaching, the Vietnam context, its interestingness, and the importance of integrating CE into STEM education. Surveyed teachers have also voluntarily integrated development issues and CE principles into STEM teaching. Including CE in STEM education in secondary education offers a promising opportunity to foster more profound societal change toward sustainable development, which contributes to SDG4 — equitable and quality education for sustainable development and sustainable lifestyles and SDG 12.5 — reduce waste generation through prevention, reduction, recycling, and reuse.